(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Computational study of 16-residue polypeptide chain is reported for its stability in structure and specificity in chemical interaction using Gromacs software. The results are observed to be in agreement with the experimental results on the same polypeptide chain.